The Effect of Flipped Classroom Model with Information Search Strategy Through Moodle-Based E-Lematika on Students' Self-Efficacy in Mathematics - Amalia Husna; Sofnidar Sofnidar (Universitas Islam Sultan Agung, 2022)
Self-efficacy has a great influence on learning outcomes and academic achievement. However, many students have low self-efficacy in mathematics. For this reason, a learning process is needed that can help improve students' self-efficacy in mathematics. This study aimed to determine the effect of the inverted classroom model with information search strategies through moodle-based e-lematika media on students' self-efficacy in mathematics. This research is a type of quantitative research with a quasi-experimental design method. The population of this research is class XI students of SMK N 1 Jambi City and two sample classes, namely 31 students of class XI TKJ 1 and 31 students of class XI TKJ 5, respectively, the experimental class and control class. The self-efficacy questionnaire data analysis for the two classes was carried out using the independent sample t-test, which showed the value of sig. (2-tailed) is 0.000 < 0.05. So, there is a significant effect on the application of the flipped classroom model with information search strategies through moodle-based e-lematika media on students' self-efficacy.